Organic Syntheses 2014
DOI: 10.1002/0471264229.os091.06
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alkynyliodonium Salts: Preparation of Phenyl(phenylethynyl)iodonium Trifluoroacetate

Abstract: Alkynyliodonium salts are highly versatile reactive intermediates and as such, have been used in a number of cycloaddition reactions including 1,3‐dipolar cycloadditions with nitrile‐oxides, diazoketones and azides as well as Diels‐Alder chemistry. This article discusses the preparation procedure of phenyl(phenylethynyl)iodonium trifluoroacetate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Alkynyliodonium salts are generally prepared by the reaction of a hypervalent iodine reagent with terminal alkynes, , or silylated, stannylated, and borylated alkynes. A one-pot procedure for preparing alkynyliodonium salts from alkynyl precursors and iodoarenes and m CPBA has been developed. ,, The crystal structure of alkynyl­(aryl)­iodonium salts has been characterized by X-ray crystallography, ,,, and it has been demonstrated that the aryl group occupies an equatorial position, whereas the alkynyl moiety and the counterion occupy apical positions. The thermal stability of alkynyl­(aryl)­iodonium salts depends on the nature of the anion and the substituent on the acetylenic β-carbon.…”
Section: Synthetic Applications Of Trivalent Iodine Compoundsmentioning
confidence: 99%
“…Alkynyliodonium salts are generally prepared by the reaction of a hypervalent iodine reagent with terminal alkynes, , or silylated, stannylated, and borylated alkynes. A one-pot procedure for preparing alkynyliodonium salts from alkynyl precursors and iodoarenes and m CPBA has been developed. ,, The crystal structure of alkynyl­(aryl)­iodonium salts has been characterized by X-ray crystallography, ,,, and it has been demonstrated that the aryl group occupies an equatorial position, whereas the alkynyl moiety and the counterion occupy apical positions. The thermal stability of alkynyl­(aryl)­iodonium salts depends on the nature of the anion and the substituent on the acetylenic β-carbon.…”
Section: Synthetic Applications Of Trivalent Iodine Compoundsmentioning
confidence: 99%